A chemical biology approach reveals a dependency of glioblastoma on biotin distribution - Yoon, Jeehyun (2022)
Glioblastoma (GBM) is a uniformly lethal disease driven by glioma stem cells (GSCs). Here, we use a chemical biology approach to unveil previously unknown GBM dependencies. By studying sulconazole (SN) with anti-GSC properties, we find that SN disrupts biotin distribution to the carboxylases and histones. Transcriptomic and metabolomic analyses of SN-treated GSCs reveal metabolic alterations that are characteristic of biotin-deficient cells, including intracellular cholesterol depletion, impairment of oxidative phosphorylation, and energetic crisis. Furthermore, SN treatment reduces histone biotinylation, histone acetylation, and expression of superenhancer-associated GSC critical genes, which are also observed when biotin distribution is genetically disrupted by holocarboxylase synthetase (HLCS) depletion. HLCS silencing impaired GSC tumorigenicity in an orthotopic xenograft brain tumor model. In GBM, high HLCS expression robustly indicates a poor prognosis. Thus, the dependency of GBM on biotin distribution suggests that the rational cotargeting of biotin-dependent metabolism and epigenetic pathways may be explored for GSC eradication.